Multiscale drug repurposing study for the treatment of the alzheimer disease: a combined in silico and in vitro study - Aljanabi, Hind (My University, 2022)
Alzheimer's disease (AD) is a central nervous system chronic condition that causes a decrease in cognitive control and language capacity. AD is associated with cholinergic deficiency, and various cholinesterase inhibitors, including naturally derived inhibitors, synthetic analogs, and hybrids have been developed to treat AD. The drugs available for AD are currently mainly cholinesterase inhibitors. However, the efficacy of these drugs was limited, as they can cause adverse side effects and are unable to stop the progression disease entirely. Initially, in the current study, 7922 small compounds were retrieved from NIH Chemical Genomics Center (NCGC) pharmaceutical collection (NPC) library to be screened through QSAR model developed from targets against AD. The molecules with higher AD therapeutic activity values (>0.75) were then used in the 26 different toxicity-QSAR models. Binary QSAR models resulted in 10 hits that have high AD therapeutic activity and no toxicity. The selected hits were then screened against acetylcholinesterase (AChE), and butyrylcholinesterase (BuChE) targets using standard precision docking (SP), induce fit docking (IFD) and quantum mechanics-polarized ligand docking (QPLD). Top IFD docking poses for five compounds were used in, initially, short (50 ns), and then long (100 ns) molecular dynamics (MD) simulations. Molecular Mechanics/Generalized Born Surface Area (MM/GBSA) binding free energy calculations were performed for the five top compounds. A similar protocol was also applied for three of the known AChE and BuChE inhibitors. Finally, based on MM/GBSA scores and their corresponding docking scores, three compounds were ordered, and their in vitro tests were performed. All compounds showed nM-level inhibition for both AChE and BuChE targets. The outcomes of this study may open a new perspective for the development of novel drugs with reduced toxicity and preserved pharmacological activity against AD.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2022
Keywords: Alzheimer disease; Acetylcholinesterase; Butyrylcholinesterase; Molecular docking; MD simulations